Repair of Full-Thickness Gluteus Maximus Tear With Suture Anchors - Ryan H. Barnes, M.D.; John Ryan, M.D.; W. Kelton Vasileff, M.D. (Arthroscopy Techniques, 2024)
Gluteal tendon tears are a common cause of hip pain. Most commonly, tears occur in the gluteus medius and minimus, and there are well-established nonoperative or operative treatment pathways. In this Technical Note, we describe our technique for repair of a full-thickness gluteus maximus tendon tear using anchor fixation.